4(x+3)+x=874(x+3)+x=87

Simple and best practice solution for 4(x+3)+x=874(x+3)+x=87 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+3)+x=874(x+3)+x=87 equation:



4(x+3)+x=874(x+3)+x=87
We move all terms to the left:
4(x+3)+x-(874(x+3)+x)=0
We add all the numbers together, and all the variables
x+4(x+3)-(874(x+3)+x)=0
We multiply parentheses
x+4x-(874(x+3)+x)+12=0
We calculate terms in parentheses: -(874(x+3)+x), so:
874(x+3)+x
We add all the numbers together, and all the variables
x+874(x+3)
We multiply parentheses
x+874x+2622
We add all the numbers together, and all the variables
875x+2622
Back to the equation:
-(875x+2622)
We add all the numbers together, and all the variables
5x-(875x+2622)+12=0
We get rid of parentheses
5x-875x-2622+12=0
We add all the numbers together, and all the variables
-870x-2610=0
We move all terms containing x to the left, all other terms to the right
-870x=2610
x=2610/-870
x=-3

See similar equations:

| -4x-3=0.5x+2 | | 250+12n=650 | | -2x-3=0.5x+2 | | -4x+6x-9=2(x-3)-6 | | 16c-9c-6c-1=16 | | -2x+8x-6=6(x-5)-1 | | (-5/2)x=5 | | 5^4x-2=25 | | -5/2x=5 | | 12(3x-1)=108 | | 36x-12=108 | | 5a+5=3a+15 | | y/5+4=5 | | ___-____=____(2t-3) | | 42x-35)-(12x-8)=1 | | 7+4a=5a | | 5(a+4)=2(a-5) | | x2+128-14x=0 | | 3(3x-12)=108 | | C=3.14×15r | | y/2+3=2 | | 30x-12=33 | | 4x-5=3x-12 | | (4y+5)(7+y)=0 | | m-2*20=10 | | 3+2x=-4x+39 | | -8x=-1-9x | | 5x+4=8x+19 | | 2x+(x+48)=90 | | 7x=9+8 | | -15=3x/7 | | x/8+1/2=1/4 |

Equations solver categories